PENERAPAN ALAT BIOGAS KOTORAN SAPI DI DESA PATTIRO DECENG, KECAMATAN CAMBA KABUPATEN MAROS - Hamri, Hamri (Jurnal BALIRESO, 2017)
The condition in the Village Pattiro Deceng depicted a great potential to manage natural resources in the era of autonomy area, where the Diffusion program and Iptek usage in remote villages can not listed in optimum. The impact desired of this program is the utilization of resources nature in the village into an energy source an alternative that is a new energy is renewable through the making biogas of cow dung. Problems facing the current partner based on the survey results conducted by the team is: Technology Right of the farm and ranch the processing dirt livestock be biogas, has the potential to be processed into biogas very large, lack of sanitation environment area cattle, Ingredients fuel for household there are still using the firewood, less information and understanding in the field of IPTEK. Deploy IbM does is lecture, then make the tool biogas training, counseling we provide is on environmental sanitation, biogas, providing a clean environment understanding of the cage, entrepreneurship, to provide knowledge of economic value when used ox dir into biogas. And effluent (the result of fermentation), given the knowledge to make solid and liquid manure.